2008
DOI: 10.1007/s00125-008-1175-9
|View full text |Cite
|
Sign up to set email alerts
|

The association of common genetic variants in the APOA5, LPL and GCK genes with longitudinal changes in metabolic and cardiovascular traits

Abstract: Aims/hypothesis Common genetic variants influence plasma triacylglycerol, HDL-cholesterol (HDL-C) and glucose levels in cross-sectional studies. However, the longitudinal effects of these established variants have not been studied. Our aim was to examine the longitudinal associations of four such variants in the apolipoprotein A-V (APOA5), lipoprotein lipase (LPL), and glucokinase (GCK) genes with fasting glucose or lipid levels. Methods The individuals analysed were participants in the Busselton Health Survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 33 publications
(36 reference statements)
1
23
1
Order By: Relevance
“…Although evidence is still limited, LPL activity seems to be modified by aging (32) and lifestyle (33) as well as by carrying particular polymorphisms in the LPL gene (34). Recent studies have reported some common polymorphisms that are significantly associated with longitudinal variations in HDL-C concentrations (35,36). In a 20-y follow-up study, Tang et al (35) observed that several common polymorphisms, including rs328 (S4473), rs326, and rs13702, in LPL are significantly 1 Log-transformed serum concentrations measured after 6 y were used.…”
Section: Discussionmentioning
confidence: 99%
“…Although evidence is still limited, LPL activity seems to be modified by aging (32) and lifestyle (33) as well as by carrying particular polymorphisms in the LPL gene (34). Recent studies have reported some common polymorphisms that are significantly associated with longitudinal variations in HDL-C concentrations (35,36). In a 20-y follow-up study, Tang et al (35) observed that several common polymorphisms, including rs328 (S4473), rs326, and rs13702, in LPL are significantly 1 Log-transformed serum concentrations measured after 6 y were used.…”
Section: Discussionmentioning
confidence: 99%
“…For C/C homozygotes, low CHO intakes were associated with an increase in plasma TG concentrations, whereas when CHO intakes were high, they had the greatest decrease in their plasma TG concentrations following the fish oil supplementation of all genotype groups. The SNP rs741038 is an intronic SNP with no potential regulatory impact and is not in LD with rs1799884 or rs2070971 which have been associated previously with plasma TG levels, fasting glucose and/or type 2 diabetes risk (Asselbergs et al 2012;Holmkvist et al 2008;Sotos-Prieto et al 2013;Webster et al 2009;Hu et al 2010;Wang et al 2013). However, it is possible that rs741038 is in LD with other unknown functional SNPs.…”
Section: Discussionmentioning
confidence: 99%
“…For lipoprotein lipase ( LPL ) related SNPlcar 23 (rs328:G/C; GG vs. CC, mainly low α -carotene (22; 30) ), two previous studies conducted among Caucasian adults also indicated that the “C” allele was consistently linked to HDL-C dyslipidemia, (63; 65) with one of them observing an additional link to TG-dyslipidemia. (65) However, a recent meta-analysis showed only a modest relationship between rs328:G/C and both types of dyslipidemia.…”
Section: Discussionmentioning
confidence: 99%
“…(65) However, a recent meta-analysis showed only a modest relationship between rs328:G/C and both types of dyslipidemia. (66) Prior to correction for multiple testing, our study was indicative of a consistent relationship in which the “G” allele was associated with a lower odds of elevated HOMA-IR (OR=0.66; 95%CI:0.44–0.98; p=0.037), ( OSM 5 ).…”
Section: Discussionmentioning
confidence: 99%